Women’s involvement in cybercrime: a premilinary study - Muhamad Asyraf Ahmad Termimi; Muhammad Ikhlas Rosele; Khairul Azhar Meerangani; Syamsul Azizul Marinsah; Mohd Anuar Ramli (CIRWOLRD, 2015)
Cyber crimes is a new millennium threat to society nowadays which brings by developments of technology and information. Various forms of cyber crimes exist either theft and fraud involving money and property or safety threat involving contamination of dignity. Therefore, this study will identify cyber crimes related to women in Malaysia for cases of theft and fraud of money and property through cyberspace. Cyber crimes will be identified and classified according to cases that often occurred in Malaysia and legal protection provided to the victim. The results showed lack of awareness about cyber security transactions and the provision of existing law that exists for cyber crime cause women to be victims of cyber crime.